The building of medial didactics for the enrichment of adult education in Peru - Rodríguez del Solar, Natalia (2014)
In the present era of Knowledge, the use of different Media in Didactics as part of the General Didactics acquires a superior importance. This is due to the high progress of science and technology. The traditional curriculum is extended beyond old edges using the “medial education” as a fundamental new component of general education. A new holistic curricular vision arises, open to the new world environment that includes the media as a leverage for the further development of society. The medial didactic creates a new environment for learning and new experiences and competencies, a new culture for teachinglearning with a vision of permanent formation. We embrace media as key curricular elements that work inside an educational context and work in relation to subjects, processes. It enhances the development of cognitive values in the students. They break traditional structures of calendars and courses and develop through new resources such as: magazines, videos, CDs, computers, tablets, building new learning processes way more cooperative and productive.